Underemployment and housing insecurity: an empirical analysis of HILDA data - Campbell, I.; Parkinson, S.; Wood, Gavin (2014)
Time-related underemployment, hereafter just called underemployment, can be broadlyunderstood as employment that is insufficient in terms of the number of hours of paid work (Campbell et al. 2013, pp.9–11, 16–18, 67–70; see ILO 2013, p.9). The concept of underemployment is closely linked to that of unemployment since both involve insufficient hours of paid work and both are identified in official statistics as aspects of labour force underutilisation. Underemployment is a widespread and persistent feature of contemporary Australian labour markets, associated with adverse consequences such as low personal income, low life satisfaction, poor skills enhancement and low family income (Watson 2008; Wilkins 2007), yet there has been little research examining its impact on housing. Given the robust literature that points to the adverse impact of unemployment, or joblessness in general, on housing security (Berry et al. 2010; Böheim & Taylor 2000; Horsewood & Doling 2004), there is a strong prima facie case that underemployment might also have adverse consequences for housing security. This in turn has implications for the design of policy aimed at easing pressures that lead to housing insecurity. This research project aims to provide an Australia-wide analysis of the consequences of underemployment for housing security. An earlier AHURI Positioning Paper (Campbell et al. 2013) details the rationale for the project, addresses important conceptual issues and reviews the academic and policy literature. This Final Report presents the empirical findings. It aims to deepen our knowledge of underemployment and its relationship to housing insecurity by answering the following research questions: 1. What is the level and trend for underemployment? 2. What are the main characteristics of underemployed individuals? 3. Is underemployment for individuals correlated with other dimensions of labour insecurity? 4. What is the pattern of persistence in underemployment? Are underemployment ‘spells’ typically short-lived or more persistent? 5. What are the main characteristics of underemployed households? 6. Do underemployed households have a higher incidence of housing insecurity compared with other household types? How does this vary with tenure? - Is the incidence of housing payment arrears and risk higher among underemployed households compared with other household employment types? - To what extent do underemployed households, compared with other household types, encounter difficulties with paying other bills? - To what extent do underemployed households, compared with other household types, use income-supplementing strategies? - Has housing affordability for underemployed households declined over time compared with other household types? 7. Do correlations between underemployment and housing insecurity outcomes still hold after controlling for other individual and household attributes? 8. Does the persistence of underemployment increase the odds of housing insecurity? 9. What might be the policy implications of the answers to the previous questions? 10. What might be the implications for further research? To answer these questions we draw on the first nine (2001–2009) waves of the Household Income and Labour Dynamics in Australia (HILDA) Survey. We analyse the HILDA data, using 2 both descriptive techniques and logistic regression modelling. Our sample design comprises those individuals within households who we consider to be responsible for meeting rents and housing payments. Using a conventional labour force framework for disaggregating the working-age population, we distinguish the underemployed, defined as persons employed parttime, that is less than 35 hours per week, who state a preference for more hours of paid work, from four other labour status groups—the full-time employed, adequately employed part-timers, the unemployed and persons not in the labour force (NLF). Building on this labour force framework, we also develop a typology that distinguishes different household types. The key categories are two underemployed household types, distinguished according to whether underemployment is present in either single-earner or multiple-earner households. Comparison categories include single- and multiple-earner households in which all workers are employed, either full-time or part-time, but none fall into the category of underemployment. These household types are described as adequately employed. Other comparison categories include two household types with unemployment present, which can be grouped with the two underemployed household types as inadequately employed, and one household type with all adults not in the labour force. To operationalise the concept of housing insecurity we use two measures—housing payment arrears and housing payment risk. Housing payment arrears is derived from the HILDA financial stress indicator: ‘could not pay the mortgage or rent on time’ in a recent period because of a shortage of money. This measure is indicative of a cash flow problem that could be either one-off or more enduring. Housing payment risk is a variation on the typical housing stress measure and flags individuals and households as ‘at risk’ if they satisfy all of the following three conditions: - Paying over 30 per cent of equivalised disposable income on rental or mortgage costs. - Extreme difficulty in raising $2000 ($3000) at a time of need. - Self-rated prosperity as ‘just getting along’, ‘poor’ or ‘very poor’.